Teaching Literature: Infusing Literary Works on Language and Emotional Intelligence Improvement - Rokhmah, Desy Eva Laila; Purwaningsih, Yuni Ratna; Anggawirya, Arin Mantara; Floriani, Rosalia (Universitas Dian Nuswantoro, 2023)
Abstract. Literary works and language teaching need more prior focus on their investigation, specifically on seeing how those two things affect language proficiency. This study aims to investigate the effectiveness of teaching literature in improving students' English proficiency while also considering other aspects such as empathy, emotional intelligence, and aesthetic satisfaction. The method used was a pre-experimental design with a sample of 28 students. Before the intervention, a needs analysis was conducted to measure students' reading literacy, reading interest, and aesthetic interaction with literature. Learning objectives designed based on this needs analysis were then implemented. The data were taken through conducting need analysis, treatment, and measurement. The findings showed a significant increase in the student's English proficiency, with approximately 82% increases in empathy scores, 35% in emotional intelligence, and 20% in aesthetic satisfaction. These results indicate that literature is an effective tool for language teaching and contributes to students' holistic development in other aspects of life.Keywords: children's literature; emotional intelligence; language development; teaching literatureAbstrak. Penelitian ini bertujuan untuk mengetahui efektivitas pengajaran sastra dalam meningkatkan kemahiran bahasa Inggris siswa, serta mempertimbangkan aspek lain seperti empati, kecerdasan emosional, dan kepuasan estetika. Metodologi yang digunakan adalah desain pra-eksperimental dengan sampel sebanyak 28 siswa. Sebelum melakukan intervensi, dilakukan analisis kebutuhan untuk mengukur literasi membaca siswa, minat membaca, dan interaksi estetika dengan sastra. Tujuan pembelajaran yang dirancang berdasarkan hasil analisis kebutuhan ini kemudian dilaksanakan. Temuan menunjukkan bahwa terdapat peningkatan yang signifikan dalam kemahiran bahasa Inggris siswa, dengan peningkatan skor empati sekitar 82%, kecerdasan emosional sebesar 35%, dan kepuasan estetika sebesar 20%. Hasil ini menunjukkan bahwa sastra tidak hanya merupakan alat yang efektif untuk pengajaran bahasa tetapi juga memberikan kontribusi terhadap perkembangan holistik siswa dalam aspek kehidupan lainnya.Kata kunci: kecerdasan emosional; perkembangan bahasa; pengajaran sastra; sastra anak